Stationary stochastic processes for scientists and engineers - Lindgren, Georg, 1940-; Rootzen, Holger; Sandsten, Maria (Boca Raton, Fl. : CRC Press, 2014)
Carefully balancing mathematical rigor and ease of exposition, Stationary Stochastic Processes for Scientists and Engineers teaches you how to use these processes efficiently. The book provides you with a sufficient understanding of the theory and a practical appreciation of how it is used in real-life situations. Special emphasis is on the interpretation of various statistical models and concepts as well as the types of questions statistical analysis can answer. Features, Explains the relationship between a covariance function and spectral density, Illustrates the difference between Fourier analysis of data and Fourier transformation of a covariance function, Covers AR, MA, ARMA, and GARCH model, Details covariance and spectral estimation, Shows how stochastic processes act in linear filters, including the matched, Wiener, and Kalman filters, Describes Monte Carlo simulations of different types of processes, Includes many examples from applied fields as well as exercises that highlight both the theory and practical situations in discrete and continuous time Book jacket.
'A Chapman & Hall book.'
Includes bibliographical references : (pages 299-303) and index.
Keywords: Stationary processes; Stochastic analysis